BASIC PRINCIPLES OF THE CONCEPT OF SPIRITUAL SPACE - Mamatkulov Eldor Safarovich (Journal Park Publishing, 2023)
This article analyzes the main principles of the concept of the New Spiritual Space put forward in the strategy of New Uzbekistan. Also, the priority tasks to be implemented in the creation of a new spiritual space have been determined.
Keywords: New Uzbekistan, Third Renaissance, new spiritual space, philosophy, principle.